2007
DOI: 10.4141/cjps07022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural light on surface temperature and lycopene content of vine ripened tomato fruit

Abstract: Helyes, L., Lugasi, A. and Pék, Z. 2007. Effect of natural light on surface temperature and lycopene content of vine ripened tomato fruit. Can. J. Plant Sci. 87: 927-929. Indeterminate round type tomato (Lycopersicon esculentum Mill.) grown on a supporting trellace system in the field was used to determine the correlation between light exposure and the surface temperature and lycopene content of tomato fruit. The positive correlation between solar radiation and surface temperature was stronger (R 2 = 0.87) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 7 publications
3
31
0
Order By: Relevance
“…This result is in good agreement with the findings of Ambrózy et al (2016). This phenomenon can be explained by the temperature conditions, as it is well known that supraoptimal temperatures can inhibit carotenoid synthesis in fruits of tomato, an another Solanaceous vegetable (Helyes et al 2007). In this study, a significant negative correlation was found between the ratio of supraoptimal temperature prior to harvest and total carotenoid content (r = -0.90, N = 12, P < 0.001).…”
Section: Total Carotenoid Contentsupporting
confidence: 81%
“…This result is in good agreement with the findings of Ambrózy et al (2016). This phenomenon can be explained by the temperature conditions, as it is well known that supraoptimal temperatures can inhibit carotenoid synthesis in fruits of tomato, an another Solanaceous vegetable (Helyes et al 2007). In this study, a significant negative correlation was found between the ratio of supraoptimal temperature prior to harvest and total carotenoid content (r = -0.90, N = 12, P < 0.001).…”
Section: Total Carotenoid Contentsupporting
confidence: 81%
“…() and Helyes et al. () even observed a reduction in β ‐carotene and lycopene contents at extremely high radiation intensities.…”
Section: Discussionmentioning
confidence: 93%
“…The contents of free amino acid were determined with ninhydrin coloration method according to [12]. The lycopene contents were measured by spectrophotometer according to [13]. The polyphenol contents were determined by the Folin-Ciocalteu procedure according to [14].…”
Section: B Fruit Quality Determinedmentioning
confidence: 99%